Training Dimensions Independence in Students Phase A P5 Activity at Marsudirini Elementary School The Place of Semarang - Hartutik Hartutik; Andarweni Astuti; Matilda Stella Pradnya; Mayang Setyaningsih; Irene Nindita Pradnya; YL Sukestiyarno (Universitas Negeri Semarang, 2024)
The purpose of this community service activity is to provide independence training to Phase A students in grades 1 and 2 of Marsudirini Elementary School, Gedangan, Semarang. The training material is intended to teach aspects of self-independence by practicing a good work culture. This activity reflects the development of the independent dimension of the Pancasila Student Profile in the Pancasila Student Profile Strengthening Project (P5). There are six P5 themes at the elementary school level, namely sustainable lifestyle, local wisdom, Bhinneka Tunggal Ika, Build Your Soul and Body, Engineering and Technology, and Entrepreneurship, all of which aim to develop children's potential as a whole, starting from cognitive, affective, psychomotor to social emotional aspects. The method of implementing this service is lectures, Q&A/discussions and practices. The results of this service activity are the knowledge and skills of Phase A students in grades 1 and 2 of Marsudirini Elementary School, Gedangan, Semarang in helping to overcome themselves in simple things, especially in terms of knowledge of first aid in accidents, can be understood and practiced independently and can reduce fear and panic.